Kendala Pembelajaran Jarak Jauh Dalam Jaringan Bahasa Mandarin SMA/MA/SMK di Jabodetabek - Zelia, Vanya; Andriani, Susi; Ramadhanty, Dwi Annisa (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
The pandemic has changed the world education and learning models around theworld. Face to face learning has turned to online distance learning, including atSMA/MA/SMK level. PJJ consists of online distance learning and offline distancelearning. Online distance leaning is using electronic media through portals and onlinelearning applications with internet network learning. This research aims to find out theobstacles facedin terms of the use of electronic media, internet, and Learning Management System(LMS) in online distance learning at SMA / MA / SMK in Jabodetabek of Mandarinteachers. This research is a survey study. The data was obtained using questionnaire.The respondents are 50 applied Mandarin learning at SMA/MA/SMK teachers inJabodetabek. The result shows that the obstacles faced by teachers are theunavailability of electronic media, limited resource in operating electronic media,electronic media does not supported by certain specifications or features, the damageof electronic media, the Operating System (OS) is not the latest, expensives internetcost, slow internet network, LMS does not supported certain featires, in additionteachers do nit understand how to operate the LMS. The results of this research can beconsidered input for education field, specifically those that are directly related toMandarin online distance learning,as well as being considered to overcome Mandarinonline distance learning.